Death of an Honest Man : Hamish Macbeth #33 - Beaton, M. C. (New York ; Boston : Grand Central Publishing, 2018)
"Sergeant Hamish Macbeth--Scotland's most quick-witted but unambitious policeman--returns in M.C. Beaton's new mystery in her New York Times bestselling series. DEATH OF AN HONEST MAN Nobody loves an honest man, or that was what police sergeant Hamish Macbeth tried to tell newcomer Paul English. Paul had moved to a house in Cnothan, a sour village on Hamish's beat. He attended church in Lochdubh. He told the minister, Mr. Wellington, that his sermons were boring. He told tweedy Mrs. Wellington that she was too fat and in these days of increasing obesity it was her duty to show a good example. Angela Brody was told her detective stories were pap for the masses and it was time she wrote literature instead. He accused Hamish of having dyed his fiery red hair. He told Jessie Currie--who repeated all the last words of her twin sister--that she needed psychiatric help. "I speak as I find," he bragged. Voices saying, "I could kill that man," could be heard from Lochdubh to Cnothan. Annd someone did. Now Hamish is faced with a bewildering array of suspects. And he's lost the services of his clumsy policeman, Charlie, who has resigned from the force after Chief Inspector Blair berated Charlie one too many times, and the policeman threw Blair into the loch. Can Hamish find the killer on his own?"--.
Keywords: Macbeth, Hamish -- (Fictitious character) -- Fiction; Police -- Scotland -- Highlands -- Fiction; Murder -- Investigation -- Fiction; FICTION / Mystery & Detective / Police Procedural; FICTION / Mystery & Detective / Traditional British; Mystery fiction